2020
DOI: 10.31616/asj.2019.0174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pedicle Screw Pullout Load Paths for Osteoporotic Vertebrae

Abstract: Study Design: A biomechanical study.Purpose: To determine the actual load path and compare pullout strengths as a function of screw size used in revision surgeries using postmortem human subject specimens.Overview of Literature: Pedicle screw fixation has become the standard of care in the surgical management of spinal instability. However, pullout failures are widely observed in osteoporotic spines and treated by revision surgeries using a higher diameter screw, performing cement augmentation, or increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The reported incidence of loosening at the screw-bone interface spans a wide range, mainly between 10 and 30%, with highest rates observed in patients with poor bone quality (Ohlin et al 1994;Abul-Kasim and Ohlin 2014;Bredow et al 2016;Kim et al 2020;Zou et al 2020). The most commonly reported cause for failed fusion is low bone mineral density (BMD) (Krishnan et al 2020), which can lead to postoperative pain and ultimately requiring revision surgery to stabilize the spinal segment.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of loosening at the screw-bone interface spans a wide range, mainly between 10 and 30%, with highest rates observed in patients with poor bone quality (Ohlin et al 1994;Abul-Kasim and Ohlin 2014;Bredow et al 2016;Kim et al 2020;Zou et al 2020). The most commonly reported cause for failed fusion is low bone mineral density (BMD) (Krishnan et al 2020), which can lead to postoperative pain and ultimately requiring revision surgery to stabilize the spinal segment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have recommended anterior reconstructive surgeries such as corpectomy with anterior fusion or circumferential fusion. [9][10][11] Anterior reconstructive surgery has yielded favorable results including a good fusion rate and kyphosis correction, but the anterior approach may cause pulmonary, intra-abdominal and retroperitoneal complications. Moreover, long operative time and greater blood loss may be a drawback considering patient age and condition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, long operative time and greater blood loss may be a drawback considering patient age and condition. 9 - 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some scholars 10 proposed that double-threaded screws and ordinary pedicle screws showed the same axial extraction force and anti-fatigue strength. Studies have shown that larger diameter screws increase the pullout strength and that the pullout strength increases 35% when the screw diameter is increased by 2 mm 11 , 23 . PMMA-PSs are one of the most common ways to prevent the failure of internal fixation in osteoporotic lumbar internal fixation surgery.…”
Section: Discussionmentioning
confidence: 99%